Frailty is associated with adverse outcome from in-hospital cardiopulmonary resuscitation. (October 2019) - Wharton, Chris; King, Elizabeth; MacDuff, Andrew
Abstract: Aim: To assess whether frailty was associated with cardio-pulmonary resuscitation (CPR) outcome in a UK setting. Method: Retrospective review of prospectively collected data on in-hospital cardio-respiratory arrests between 1/1/17 and 31/12/17. Clinical Frailty Scale (CFS) scores were assigned from notes review, patients with CFS scores ≥6 signified moderate or greater frailty. Results: There were 179 in-hospital cardiac arrest cases where the CFS could be calculated. The median age on admission was 74 (mean 71, range 27–102), 110 patients were male and 69 female. The initial rhythm was non-shockable in 64% of cases. In 49% of cases return of spontaneous circulation (ROSC) was achieved, 22% of the study population survived to hospital discharge. Moderate or greater frailty was present in 31.3% of patients. Return of spontaneous circulation (ROSC) was achieved in 56.1% of patients with a CFS score of 1–5 and 32.1% with scores 6–9 ( p < 0.001). Survival to hospital discharge was also associated with frailty, being seen in 31.7% of CFS 1–5 patients but only in 1.8% of CFS 6–9 patients ( p < 0.001). In multivariable analysis adjusting for age, presenting rhythm and admitting specialty the effect of frailty on survival to discharge remained significant ( p = 0.044). Conclusion: Patients with moderate or greater frailty as determined by CFS score are unlikely to survive to hospital discharge even if ROSC occurs following CPR. This should be considered when making resuscitation status and ceiling of care decisions in this patient group.